Preoperative surgical risk stratification in osteosarcoma based on the proximity to the major vessels. (August 2019) - Fujiwara, T.; Medellin, M. R.; Sambri, A.; Tsuda, Y.; Balko, J.; Sumathi, V.; Gregory, J.; Jeys, L.; Abudu, A.
Abstract : Aims: The aim of this study was to determine the risk of local recurrence and survival in patients with osteosarcoma based on the proximity of the tumour to the major vessels. Patients and Methods: A total of 226 patients with high-grade non-metastatic osteosarcoma in the limbs were investigated. Median age at diagnosis was 15 years (4 to 67) with the ratio of male to female patients being 1.5:1. The most common site of the tumour was the femur (n = 103) followed by tibia (n = 66). The vascular proximity was categorized based on the preoperative MRI after neoadjuvant chemotherapy into four types: type 1 > 5 mm; type 2 ≤ 5 mm, > 0 mm; type 3 attached; type 4 surrounded. Results: Limb salvage rate based on the proximity type was 92%, 88%, 51%, and 0% for types 1 to 4, respectively, and the overall survival at five years was 82%, 77%, 57%, and 67%, respectively (p < 0.001). Local recurrence rate in patients with limb-salvage surgery was 7%, 8%, and 22% for the types 1 to 3, respectively (p = 0.041), and local recurrence at the perivascular area was observed in 1% and 4% for type 2 and 3, respectively. The mean microscopic margin to the major vessels was 6.9 mm, 3.0 mm, and 1.4 mm for types 1 to 3, respectively. In type 3, local recurrence-free survival with limb salvage was significantly poorer compared with amputation (p = 0.025), while the latter offered no overall survival benefit. In this group of patients, factors such as good response to chemotherapy or limited vascular attachment to less than half circumference or longitudinal 10 mm reduced the risk of local recurrence. Conclusion: The proximity of osteosarcoma to major blood vessels is a poor prognostic factor for local control and survival. Amputation offers better local control for tumours attached to the blood vessels but does not improve survival. Limb salvage surgery offers similar local control if the tumour attachment to blood vessels is limited. Cite this article: Bone Joint J 2019;101-B:1024–1031.